Credit reporting systems and the international economy - Miller, Margaret J., 1963- (MIT Press, 2003)
"Credit reporting is a critical part of the financial system in most developed economies but is often weak or absent in developing countries. It addresses a fundamental problem of credit markets: asymmetric information between borrowers and lenders that can lead to adverse selection and moral hazard. The heart of a credit report is the record it provides of an individual's or a firm's payment history, which enables lenders to evaluate credit risk more accurately and lower loan processing time and costs. Credit reports also strengthen borrower discipline, since nonpayment with one institution results in sanctions with others."